Islam dan Moderasi Beragama - Dila Arni Putri; Khuzaifah, Khuzaifah; Novianda, Novianda Rezki Putri; Sindi Klaudia; Muhajir Darwis (La-Tahzan: Jurnal Pendidikan Islam, 2024)
The issue of Islam and religious moderation is a complex topic that requires deep understanding. Religious moderation in the Islamic context refers to a more balanced and tolerant approach to Islamic teachings, which avoids extremism and fanaticism. This study delves into the concept of religious moderation in Islam, known as wasatiyah, and its relevance in the contemporary world. Religious moderation, emphasizing balance, tolerance, and a middle-ground approach, is deemed crucial in confronting the escalating challenges of radicalism and extremism. Employing a qualitative approach, the study analyzes literature and conducts interviews with religious scholars, academics, and practitioners of religious moderation from diverse Muslim nations. The findings reveal that applying the principles of religious moderation can bolster social harmony, enhance interfaith dialogue, and foster a more peaceful and inclusive society. The study also identifies challenges in implementing religious moderation, including resistance from extremist groups and a lack of public understanding of the concept. It recommends integrating wasatiyah values into religious education and public policy to promote a more tolerant, inclusive, and just society. Additionally, it encourages collaboration between governments and civil society organizations in promoting religious moderation.